Using argument notation to engineer biological simulations with increased confidence - Alden, Kieran (2015)
© 2015 The Authors. Published by the Royal Society under the terms of the Creative Commons Attribution License http://creativecommons.org/licenses/by/4.0/, which permits unrestricted use, provided the original author and source are credited.